Analysis Of The Views Of Students Of Social Science Study Program UIN Sunan Kalijaga Yogyakarta On Hadith (Educational and Sociological Perspectives) - Jihad, Moh Iqbal Fachrullah Abul; Latipah, Eva; Suryana, Yayan (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This research originated from the author's observation of social science students UIN Sunan Kalijaga Yogyakarta in understanding Hadith through ulumul Hadith courses. From these observations, it was found that various views of students on Hadith as a source of Islamic religious teachings after the Qur'an. It also found challenges experienced by students in understanding the Hadith. This study aims to describe the views of students on the Hadith and the challenges faced by students in understanding the Hadith as one of the sources of Islamic teachings. This research is qualitative. The approach used in this study is education and sociology. The data sources of this study are primary and secondary data. Primary Data were obtained directly from interviews with the students concerned, secondary data were obtained from observation and documentation, collecting references related to the theme of this study. Data analysis techniques using data reduction, presentation, and verification of data. Checking the validity of the data in this study using triangulation data techniques. The results of this study indicate that the views of UIN Sunan Kalijaga social science students on Hadith as a source of Islamic religious teachings are very good, but in practice, social science students still have some challenges in understanding Hadith. The main challenge is the limited ability of students to understand the Hadith both in terms of text and context. Keywords: Hadith, Student Views, Educational Perspectives, Social Perspectives, Challenges.